Quality Malaysian English Language Teachers: Examining A Policy Strategy - Kepol, Napisah (Universiti Utara Malaysia Press, 2017)
Purpose - The purpose of this paper is to examine and discuss one of the strategies in the latest Malaysian language education policy Memartabatkan Bahasa Malaysia Memperkukuh Bahasa Inggeris (MBMMBI) (To Uphold Bahasa Malaysia and to Strengthen the English Language). The strategy in focus is aimed at improving the quality of English language teachers. This strategy is examined in light of selected research findings and other information that is deemed relevant to a beneficial discussion of the topic.